RANCANG BANGUN PENGUKUR SUHU TUBUH MANDIRI TANPA SENTUH SEBAGAI FASILITAS ADAPTASI KEBIASAAN BARU - Hamdani, Hamdani; Tharo, Zuraidah; Aryza, Solly (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The adaptation of new habits related to efforts to break the chain of the spread of the corona virus (covid-19) requires supporting devices, one of which is a body temperature measuring device, a body temperature measuring device commonly used by the community is a body temperature measuring device, a gun model (thermo gun), One of the weaknesses of this thermo gun measuring device is the need for a special officer to measure a person's body temperature. In the research that has been done, the researchers have sufficiently built a body temperature measuring instrument independently and without touch, the user will bring the palm of the hand closer to the temperature sensor, then the system will do it. measurement process and displays the measured body temperature value through a running text display. From the results of the temporary testing that was carried out when this article was written, it can be seen that this body temperature measuring device is able to show the display through the text that is running according to the planning being carried out. This tool can be applied to meeting rooms, offices, schools and the like, as a new habit facility.